EFEKTIVITAS MODEL PEMBELAJARAN PEMECAHAN MASALAH DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS MATEMATIS MAHASISWA PGSD - Muanifah, Mahmudah Titi; Rhosyida, Nelly (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
This study is aimed to determine the effectiveness of problem-solving learning in terms of mathematic critical thinking skills of the student in PGSD Sarjanawiyata Tamansiswa University. This study is quantitative research in the form of quasi-experiments with pretest-posttest control group research design. The population of this study is all students of the year 2016/2017 PGSD UST Yogyakarta. The experimental class and control class that taken at random are class C and class D. This research was conducted in April 2017 in PGSD UST Yogyakarta. The instrument of this study is the critical mathematical thinking skills test. instruments test were tested for validity using KMO and Bartlette's Test and reliability by using Cronbach's Alph. The data of the critical mathematical thinking test were analyzed using the SPSS program. Based on the hypothesis test, it can be concluded that the mathematics learning outcomes of students who are treated with problem-solving learning are as good as the students' mathematics learning outcomes treated with conventional learning. The results of mathematics learning students who have high critical thinking skills are better than the mathematics learning outcomes of students who have middle critical thinking skills is better than the low critical thinking skills. In the model of problem-solving and conventional learning, students' mathematics learning outcomes that have high critical thinking skills, medium and low are equally good. In categories of high, moderate, or low critical ability levels, student learning outcomes are equally good.Ã‚Â